2020
DOI: 10.24820/ark.5550190.p011.297
|View full text |Cite
|
Sign up to set email alerts
|

An expedient synthesis of novel bis[thienopyridines] linked to arene or heteroarene core as novel hybrid molecules

Abstract: A series of novel bis (thieno[2,3-b]pyridines) based arenes or heteroarenes have been synthesized from the appropriate bisbromoacetyl derivatives upon treatment with the corresponding 2-mercaptonicotinonitrile derivatives in ethanolic sodium ethoxide at reflux. Attempts to synthesize these compounds via bis-alkylation of the appropriate phenol derivative with the corresponding dibromo compounds using a mild base were unsuccessful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…It is suggested that compound 17 was formed initially and then intramolecular cyclocondensation of the methylene group with the ketonic groups at the 2-position of thienopyridine leading to the formation of the corresponding 2-bezofuranyl derivative 18 followed by hydrolysis and subsequent decarboxylation under the reaction conditions to give 19 . Similar behavior of some related systems has been previously reported …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…It is suggested that compound 17 was formed initially and then intramolecular cyclocondensation of the methylene group with the ketonic groups at the 2-position of thienopyridine leading to the formation of the corresponding 2-bezofuranyl derivative 18 followed by hydrolysis and subsequent decarboxylation under the reaction conditions to give 19 . Similar behavior of some related systems has been previously reported …”
Section: Resultssupporting
confidence: 89%
“…Similar behavior of some related systems has been previously reported. 82 It is worth mentioning that treatment of 15a under similar conditions gave a mixture of nonisolable products.…”
Section: ■ Introductionmentioning
confidence: 96%